2021
DOI: 10.21203/rs.3.rs-274197/v1
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: Examining and Investigating the Impact of Demographic Characteristics and Chronic Disease with Mortality of COVID-19: Retrospective Study

Abstract: Background: The COVID-19 pandemic has burdened hospitals globally and there is currently no proven treatment available. The purpose of the study was to investigate whether demographic characteristics (age and gender) and non-communicable diseases (hypertension and diabetes mellitus) have a significant association with mortality in COVID-19 patients. Methods: This is a retrospective design where we used descriptive and inferential analysis have been employed to analyze the data. Binary logistic regression was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The COVID-19 patients with coexisting IHD had a 70% higher risk of death compared with the others. The increased incidence and severity of COVID-19 among older male patients could be explained because of the high rate of comorbidities (such as hypertension) in older males [ 13 , 20 , 21 ]. Furthermore, the link between hypertension and COVID-19 severity is also linked to the use of ACE inhibitors as ACE2 serves a role in SARS infections [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 patients with coexisting IHD had a 70% higher risk of death compared with the others. The increased incidence and severity of COVID-19 among older male patients could be explained because of the high rate of comorbidities (such as hypertension) in older males [ 13 , 20 , 21 ]. Furthermore, the link between hypertension and COVID-19 severity is also linked to the use of ACE inhibitors as ACE2 serves a role in SARS infections [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that many countries around the world have been affected differently by the COVID-19 infection, ranging from a high incidence and high mortality rates in countries such as the United States, France and Spain to a low incidence and mortality rates in countries such as New Zealand [ 8 , 9 ]. These findings indicate the importance of investigating different populations around the world to gain a greater insight into the disease and to understand the impact of COVID-19 among different regions [ 8 ] as well as enabling us to be scientifically better equipped to handle similar future emergencies [ 12 , 13 ]. The present study aimed to conduct a nationwide multicenter study centered upon severely ill COVID-19 patients admitted to intensive care units (ICUs) in Saudi Arabia, assessing their clinical characteristics and prognosis.…”
Section: Introductionmentioning
confidence: 99%